Effect of load variations in DC-DC converter - Husna, A. W. N.; Siti Fatimah, Siraj, Prof. Madya. Dr.; Mahathir, H. Mat (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/